Вихретоковый магнитный сканер для визуализации металлических предметов в системах безопасности - Поповский, В. В.; Павлов, П. П.; Павлов, В. П. (ХНУРЭ, 2008)
At present for defense objects from carry weapons by foreign company were development wide spectrum of the eddy current metal detectors. The basic objects which to decide by their creation is a definition spatial location and selective detection of metallic or include metal objects of search that is weapons on background of the metal objects personal using witch have visitors. Though all effort developer this problem heretofore in full not decide. For solve this problems we have development eddy current magnetic scanner- imager. Use eddy current magnetic scanner-imager provide possibility not only determining location metal objects imageiy their form(magnetic portrait) metal classification from which it make but still at this single valued decade question selection(weapon not weapon) to the received image of objects. Обнаружение проводящих объектов в непроводящей среде с использованием магнитных методов характерно для многих направлений деятельности человека. Магнитные методы поиска с использованием металлодетекторов сегодня применяются в рудной электроразведке, дефектоскопии, в системах контроля доступа для обнаружения взрывных устройств и оружия, системах предотвращения хищений и т.д.
Keywords: металлодетектор; рудная электроразведка